2021
DOI: 10.4049/jimmunol.2100565
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 as a Th2 Cytokine: Differences Between Mice and Humans

Abstract: The discovery of IL-10 more than 30 years ago marked the beginning of our understanding of how cytokines regulate immune responses, based on cross-regulation between Th1 and Th2 cytokines. Although multiple cell types were shown to produce IL-10, its identity as a Th2 cytokine remained strong because it was rigidly associated with Th2 clones in mice, whereas both Th1 and Th2 clones could secrete IL-10 in humans. However, as new Th1/Th2 cell functionalities emerged, anti-inflammatory action of IL-10 gained more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 176 publications
0
25
0
2
Order By: Relevance
“…The increase of IL-10 might directly induce the suppression of Th1 cytokines, as previously described [ 43 ]. Indeed, IL-10 is considered as a potent immune regulatory cytokine [ 44 ]. Even though our data did not clarify the origin of IL-10, it can be considered that antigen-presenting cells, chiefly monocytes are the main source of IL-10 in our setting due to the short incubation period.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of IL-10 might directly induce the suppression of Th1 cytokines, as previously described [ 43 ]. Indeed, IL-10 is considered as a potent immune regulatory cytokine [ 44 ]. Even though our data did not clarify the origin of IL-10, it can be considered that antigen-presenting cells, chiefly monocytes are the main source of IL-10 in our setting due to the short incubation period.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant positive correlation between the expression levels of P3H1 and GATA3 using the GEPIA2 website analysis ( Figure S5A ). We then revealed that P3H1 was also significantly positively related to IL10 (Th2 cytokine) [ 24 ]. These results further confirm our findings above ( Figure S5B ).…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of several cytokines could be due to the overall decrease in the inflammatory process and, therefore, to a reduced involvement of active immune cells. In many cases, however, TNF-α and IL-10 are antagonists since the increased production of TNF-α increases the production of IL-10, creating a negative-feed loop that results in the subsequent reduction of TNF-α [ 39 , 40 , 41 ]; IL-10 is considered as an anti-inflammatory cytokine, yet that could be an oversimplification [ 42 ]. However, several interactions influence the production of IL-10 aside from TNF-α, and most relate to cytokines involved in the Th1/Th2 balance, such as IFN-γ.…”
Section: Discussionmentioning
confidence: 99%